Antenna compression using binary phase coding: an imaging application - Woodman Pollitt, Ronald Francisco (2000)
Very often one has a radar experiment with a conflicting demand. On the one hand one would like to illuminate the target with all the high power usually available with a big antenna; but on the other hand one would also like to have the broadest beam possible (i.e., smallest antenna section). Usually both situations are not compatible and one has to compromise one for the other. This problem is present, for instance, when one has a phased array with a single high power transmitter (e.g., the Jicamarca Incoherent scatter radar), where the total high power cannot be transmitted with single antenna elements. A even stronger constrain is present if one has a phased array with distributed transmitters (e.g., the Middle and Upper atmosphere (MU) VHF radar in Japan or the Buckland Park MF radar in Australia). Normally, for a given installation, i.e., fixed transmitter power level per module, and fixed number of modules (antenna size), going to smaller antennas not only implies broader antenna beams, but unfortunately also a reduction on the total transmitter power. In this paper we present a solution to overcome this limitation, i.e., transmit with a wide beam and all the available power. Our scheme is based on complementary binary phase coding of the antenna elements in a similar fashion to phase coding used in pulse compression [e.g., Farley, 1985]. The decoding part is done by software by adding the statistics of each of the coded signal, so no extra burden is added to the processing other than a few summations.